Doblaje de voz para hispanoamérica: el caso peruano - Gonzales Céspedes, Jair de Jesús (2020)
The subject of voice dubbing has been little explored in Peru. Although there is currently a study on the processes followed by one of the existing dubbing companies in the country, there are still many other points to address related to this topic. The main objective of this research was to explain the causes of the absence of a dubbing industry among us, through a study with a qualitative approach and descriptive scope. In search of the objectives, we used two research instruments: interviews with people related to dubbing in Peru and nationals of other countries where dubbing was done for Hispanic America; and the content analysis of four films dubbed in Peru and another four dubbed in Mexico. The results of the investigation showed that the non-existence of a dubbing industry in Peru, in past decades, was due to reasons such as the unfair payment to dubbing actors and the economic crisis of the mid-1980s, a situation different from that of the today, where the performance of current peruvian dubbing companies stands out due to their international achievements and the best quality of their productions.